Pengaruh Tata Letak dan Display Produk Terhadap Penjualan Sparepart Komputer di Bandung Trade Mall - Sagiri, Mohammad Ari Sholeh; Apriadi, Deri (Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
This study aims to analyze the effect of store layout and product display on computer spare part sales at Bandung Trade Mall. The background of this study is based on the increasing competition in the computer retail business, which requires effective visual merchandising strategies to attract consumers. The research method used a quantitative approach with a survey of 20 respondents selected purposively. Data were collected through questionnaires, observations, and informal interviews, then analyzed using multiple linear regression. The results show that store layout and product display have a significant simultaneous effect on sales with an F value of 12.43; sig. < 0.05. The coefficient of determination (R²) of 0.62 indicates that both variables explain 62% of the variation in sales, while the rest is influenced by other factors outside the model. These findings reinforce the S-O-R theory that visual stimuli can increase consumer comfort, interest, and impulse buying. This study has practical implications for computer retailers to optimize store layout and product display as a strategy to improve sales performance.